The Relationship Between Multiple Intelligences And Learning Styles Among Sciences And Techniques Of Physical And Sport Activities Institute Students - Chafaa , Amina; Boutalbi, Ben Djadou (sports creativity, 2025)
This study aimed for investigating the relation between multiple intelligences and learning styles of sciences and techniques of physical and sport activities Institute students. A sample of (115) male and female students representing university levels and faculties was chosen for this purposend, the sample was selected randomly . We used index learning styles and Mckenzie's (1999) multiple intelligences Inventory; The data was analyzed using the Statistical Package for the Social Sciences (SPSS) for Windows (version 21). The results showed that there is statistically significant relationship between the learning styles and multiple intelligences, The relationship appears between active style and bodily-kinesthetic intelligence , and also between active style and Interpersonal intelligence , and between reflective style and Interpersonal intelligence , and between visual style and Interpersonal intelligence, and between verbal style and Interpersonal intelligence, and between learn style verbal and Spatial intelligence, the eight learning styles influenced and were influenced by the nine intelligences